Efektivitas Badan Arbitrase Syariah Dalam Sengketa Konsumen Pada Fatwa DSN-MUI Tentang Online Shop - Novriansyah, Yudhi; Usdeldi (STIS DAFA MATARAM, 2024)
This research aims to examine the Effectiveness of the Sharia Arbitration Board in Consumer Disputes based on the DSN-MUI Fatwa regarding Online Shops. Considering the tendency of consumers to resolve consumer disputes through out-of-court channels (Non Litigasi). Using a qualitative descriptive method, this research examines related journals, compares research findings, and analyzes relevant regulations and fatwas. The research results indicate that there are still weaknesses in the Sharia Arbitration Board in resolving consumer disputes, including: the dispute resolution process requiring the agreement of both parties, the weak legal force of the decisions, limited legality, limited infrastructure that does not reach all of Indonesia, the need for reliable human resources for Sharia arbiters who understand online business issues, and the acceptance and legitimacy from the wider community